Pengaruh Karakteristik Wirausaha, Modal Usaha dan Tenaga Kerja Terhadap Keberhasilan UMKM : Studi Kasus pada Usaha Sektor Makanan dan Minuman di Kawasan MM2100 (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of entrepreneurial characteristics, business capital, and labor on the success of MSMEs in the food and beverage sector operating in the MM2100 industrial area. The research method used is quantitative with a survey approach. The research sample was taken purposively with the criteria of MSME actors who have been operating for at least one year, the sample in this study was 50 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that entrepreneurial characteristics, labor and business capital have a significant influence on the success of MSMEs in the food and beverage sector in the MM2100 area. Partially, the three variables also contribute significantly. This finding emphasizes the importance of developing entrepreneurial capacity, adequate access to capital, and improving the quality of the workforce in encouraging the success of MSMEs.